Replacing the Serious Fraud Office: The case for a new approach to serious economic crime - Mark Button; Branislav Hock; David Shepherd (Institute of Economic Affairs (IEA), 2024)
The Serious Fraud Office has experienced regular criticism and periodic scandals related to its operation, which have often led to calls for serious reform through to abolition. The Serious Fraud Office should be reformed into a Serious Economic Crime Office (SECO) with a wider remit covering prevention, the capacity to use more regulatory sanctions and the ability to build a stronger relationship with the private sector. SECO should embrace the holistic use of alternative justice mechanisms, using deferred prosecution agreements more widely, establishing a leniency programme, creating a register of serious economic crime offenders and using larger fines. SECO should undertake a much more significant role in the advancement of economic crime prevention through the development and promotion of good practices and, in the most extreme cases, 'Ethics orders', which can be targeted at corporations to implement ethics and compliance programmes. There is a gap in supporting SME victims of economic crime, and the resources and role in prevention of the new SECO should be utilised to provide support to this group in enhancing their resilience and resources in some cases to pursue relevant litigation. The new SECO should also work much more closely with private actors - who are already the most significant in tackling economic crime - to enhance its and the private sector's capabilities through accreditation and standards, staff exchanges and some contracting out of investigations through approved structures to maintain separation of powers.
Keywords: 330